Adhemar de Barros: práticas e tensões políticas no poder - Couto, Ari Marcelo Macedo (2007)
The São Paulo politics always disclosed great leaderships, amongst which Adhemar de Barros. Influential us half politicians, Adhemar were the only one that he governed Are Pablo for three mandates: 1938, 1947 and 1963. Popular, he was next to the people, thus guaranteeing its hegemony politics. Adhemar remains in the politics up to 1966, when it is moved away from the power for the military; the same ones that it supported in 1964, when of the military blow